What is the role of scientists in meeting the environmental challenges of the twenty-first century? - Richard D. Gregory; Jon Bridle; Jeremy D. Wilson (Royal Society Open Science, 2024)
We live at a time of rapid and accelerating biodiversity loss and climate change that pose an existential risk to the environment, humanity, and social justice and stability. Governmental responses are seen by many citizens, including scientists, as inadequate, leading to an increase in civil protests and activism by those calling for urgent action to effect change. Here we consider the role(s) of scientists in responding to those challenges and engaging with policy given that when a scientist moves into political advocacy, reflecting their values and preferences, their objectivity and the value of scientific opinion may be seen as compromised. We then consider whether institutional setting and career stage may affect decisions to engage with policy or activism. Against this backcloth, we ask whether it is sufficient for scientists to act as impartial ‘brokers’ in societal decisions, arguing they should consider acting as ‘Honest Advocates’ in policy formation in some circumstances. Such advocacy can contribute to decision-making in a purposeful, well-informed manner, doing societal good without damaging the reputation of science. We encourage scientists to each reflect on their multiple roles in addressing the environmental challenges of our time.